Diagnostico de la nefropatia mesangial por iga - Rodas Matute, Karol Nataly (Machala : Universidad Técnica de Machala, 2019)
INTRODUCTION: nephropathy Mesangial IgA (IgAN), also known as Berger's disease has become in recent years a major medical problem have long-term prognosis uncertain and may lead the patient to CKD Terminal, reaching including dialysis and kidney transplant. OBJECTIVE: To establish the diagnosis of Mesangial Nephropathy due to IgA, through the review of scientific literature, for the effective management of this pathology. METHODOLOGY: A bibliographic search of Institutional Databases and databases of scientific information was carried out, taking into account in the present work articles published from 2015 to December 2018. CONCLUSIONS: For the diagnosis of IgA nephropathy Mesangial, should take into account the patient's clinical, such as hematuria, macroscopic and microscopic, in some cases acute renal failure and proteinuria. As for diagnostic methods, the Standard Gold for the diagnosis of Iga Nephropathy is the renal biopsy, which despite being an invasive method, gives us the certainty of the diagnosis and severity of it. There are also several biomarkers as urinary interleukin-6 / epidermal growth factor (EGF) / IL-6 serum IgA galactose, CD89, between serum and urine biomarkers that are associated with histological findings of gravity.
INTRODUCCION: La Nefropatía Mesangial por IgA (NIgA), conocida también como la Enfermedad de Berger se ha convertido en los últimos años un problema médico importante por tener un pronóstico incierto a largo plazo, pudiendo llevar al paciente a la Insuficiencia Renal Crónica Terminal, llegando inclusive a diálisis y trasplante renal. OBJETIVO: Establecer el diagnóstico de la Nefropatía Mesangial por IgA, mediante la revisión de literatura científica, para el eficaz manejo de dicha patología. METODOLOGIA: Se realizó una búsqueda bibliográfica de bases de Datos Institucionales y bases de datos de información científica, tomándose en cuenta en el presente trabajo artículos publicados desde el año 2015 hasta Diciembre de 2018. CONCLUSIONES: Para el diagnóstico de la Nefropatía Mesangial por IgA, se debe tener en cuenta la clínica del paciente, como hematuria, macroscópica y microscópica, en algunos casos el fracaso renal agudo y la proteinuria. En cuanto a los métodos de diagnóstico el Gold Estándar para el diagnostico de la Nefropatía por Iga, es la Biopsia renal, que a pesar de ser un método invasivo, nos da la certeza del diagnóstico y gravedad de la misma. También existen varios biomarcadores como la interleucina urinaria-6/factor de crecimiento epidermal (EGF)/IL-6, suero galactosa-IgA, CD89, entre biomarcadores en suero y orina que se encuentran asociados a hallazgos histológicos de gravedad.
Keywords: NEFROPATIA MESANGIAL POR IGA; NIGA; ENFERMEDAD DE BERGER; DIAGNOSTICO